Radio journalism as research – a Ph.D. model. (1st October 2014) - Lindgren, Mia
Practice-based research methods have opened up opportunities for radio journalism academics to have their radio practice recognized as academic research. Using the example of an Australian practice-based Ph.D. project, this article presents an innovative model for higher degree research in radio, reflecting on the project's research question, methodology and structure incorporating both text and audio. This article argues for radio production as a form of qualitative methodology for collecting data and as a way to present research findings to a broader audience outside academia. Informed by Candy's (2006) framework for practice-based and practiceled research, the Ph.D. study applied two research approaches: research through practice and research on practice. To demonstrate research through practice, the researcher produced a 54-minute radio documentary, Deadly Dust, commissioned by Australian Broadcasting Corporation's (ABC) Radio National network. The 'doing' – the making of the documentary – was then contextualized and analysed through a reflexive process informed by fieldwork interviews with internationally renowned radio producers. The research on practice component of the Ph.D. dissertation accompanying the radio documentary provided new theoretical insights into the creative process of long-form radio. By demonstrating how practice can be defined in research terms, this article provides justification for the inclusion of long-form journalism, in this case a radio documentary, as a legitimate academic research output.